Improving the Understanding of the Concept of Multiplication and Division With the Aid of Kalgi Pintar Media for Students of Grade II of SD 4 Karangbener - Yovita Diva Hapsari; Melina Rahayu Nengsih; Diana Ermawati (Penerbit Hellow Pustaka, 2024)
The motivation for this issue arises from students' limited understanding of multiplication and division concepts demonstrated during mathematics lessons. This was confirmed through interviews and observations, where 13 out of 18 students did not pass daily assessments (72%). The purpose of this study was to describe the improvement in understanding multiplication and division concepts using the Kalgi Pintar instructional media in Grade II at SD 4 Karangbener. Kalgi Pintar is a teaching board media designed to assist students in comprehending multiplication and division concepts in Mathematics by applying the Kalgi Pintar (Multiply Divide Smartly) instructional approach. Conceptual understanding involves the ability to comprehend material and then express it in different forms. This Classroom Action Research (CAR) was conducted in Grade II at SD 4 Karangbener with 18 student participants. The study spanned two cycles, each consisting of two sessions, including planning and implementation, observation, and reflection. Research instruments included observation sheets, interview guidelines, and concept comprehension tests. Content validity was assessed. Data collection methods involved tests, observations, interviews, and documentation. Quantitative and qualitative data analysis methods were employed. The results of this study indicate an improvement in understanding multiplication and division concepts with the assistance of the Kalgi Pintar instructional media. In Cycle I, the achievement percentage was 28%, which increased to 78% in Cycle II. Therefore, it can be concluded that there was an enhancement in students' conceptual understanding of multiplication and division using the Kalgi Pintar media.